Letter - Joint Dispute Committee, Portsmouth, 11 May 1926 (Portsmouth)
1926-05-11 "Letter - Joint Dispute Committee, Portsmouth, 11 May 1926" [g0288001.jpg], 11 May 1926, Goodchild, W Local Organisation